A Meta-Analysis of Adenosine A2A Receptor Antagonists on Levodopa-Induced Dyskinesia In Vivo - Wang, Wen-Wen; Zhang, Man-Man; Zhang, Xing-Ru; Zhang, Zeng-Rui; Chen, Jie; Feng, Liang; Xie, Cheng-Long (Frontiers in Neurology, 2017)
Background Long-term use of levodopa (l-dopa) is inevitably complicated with highly disabling fluctuations and drug-induced dyskinesias, which pose major challenges to the existing drug therapy of Parkinson’s disease. Methods In this study, we conducted a systematic review and meta-analysis to assess the efficacy of A2A receptor antagonists on reducing l-dopa-induced dyskinesias (LID). Results Nine studies with a total of 152 animals were included in this meta-analysis. Total abnormal involuntary movements (AIM) score, locomotor activity, and motor disability were reported as outcome measures in 5, 5, and 3 studies, respectively. Combined standardized mean difference (SMD) estimates were calculated using a random-effects model. We pooled the whole data and found that, when compared to l-dopa alone, A2A receptor antagonists plus l-dopa treatment showed no effect on locomotor activity (SMD −0.00, 95% confidence interval (CI): −2.52 to 2.52, p = 1.0), superiority in improvement of motor disability (SMD −5.06, 95% CI: −9.25 to −0.87, p = 0.02) and more effective in control of AIM (SMD −1.82, 95% CI: −3.38 to −0.25, p = 0.02). Conclusion To sum up, these results demonstrated that A2A receptor antagonists appear to have efficacy in animal models of LID. However, large randomized clinical trials testing the effects of A2A receptor antagonists in LID patients are always warranted.